2020
DOI: 10.1038/s41467-019-14103-3
|View full text |Cite|
|
Sign up to set email alerts
|

Acquisition, transmission and strain diversity of human gut-colonizing crAss-like phages

Abstract: CrAss-like phages are double-stranded DNA viruses that are prevalent in human gut microbiomes. Here, we analyze gut metagenomic data from mother-infant pairs and patients undergoing fecal microbiota transplantation to evaluate the patterns of acquisition, transmission and strain diversity of crAss-like phages. We find that crAss-like phages are rarely detected at birth but are increasingly prevalent in the infant microbiome after one month of life. We observe nearly identical genomes in 50% of cases where the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 53 publications
6
30
0
Order By: Relevance
“…intestinalis pair as a model. We observed that, similarly to metagenomic findings from the human gut (6,8), a monoxenic mouse model was able to support long term and stable persistence of ΦcrAss001. Bacterial clones recovered from colonised mice showed varied degree of resistance to phage, but no obvious cost with regards to bacterial population density was associated with phage colonisation.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…intestinalis pair as a model. We observed that, similarly to metagenomic findings from the human gut (6,8), a monoxenic mouse model was able to support long term and stable persistence of ΦcrAss001. Bacterial clones recovered from colonised mice showed varied degree of resistance to phage, but no obvious cost with regards to bacterial population density was associated with phage colonisation.…”
Section: Discussionsupporting
confidence: 70%
“…A recent longitudinal study of the human gut virome highlighted long-term (months and even years) high-level persistence of different combinations of crAss-like phages across individuals (6). When vertically transmitted from mothers to their infants or transplanted into in the course of faecal microbial transplantation (FMT), crAss-like phage engraft successfully and stably persist for many months (7,8). CrAss-like phages can also persist in pure bacterial culture in vitro over many serial passages without any significant effect on the density of host population (9).…”
Section: Introductionmentioning
confidence: 99%
“…The group of crAss-like phages and their high prevalence and abundance across human gut viromes have been described extensively [37], [76], [99], [100]. Although not as widespread as the crAss-like phages, the newly discovered LoVEphage seems to be rather common as well, with a prevalence of 28.6% in the healthy Danish subjects, and 14.4% in the SRA viromes (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…The presence of CrAssphage in the gut appears to begin in infancy (McCann et al, 2018;Edwards et al, 2019;). It appears to be transmitted vertically, with homology found between isolates from mother and child (Siranosian et al, 2020), which also corresponds with the presence of its Bacteroides host (Tanaka and Nakayama, 2017). However, there is again a large degree of inter-individual variation in the presence and abundance of CrAssphage.…”
Section: Identification Of Novel Human Phagesmentioning
confidence: 98%